(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Moxifloxacin (MOX) is a fluoroquinolone antibiotic, a second-line anti-TB drug widely used in the treatment of multidrug-resistant tuberculosis (MDR TB) and drug-susceptible TB. MOX have taste and smell issues with low patient compliance, especially in the pediatric population. MOX taste-masked dispersible tablets were developed by direct compression method using mannitol, aspartame as a sweetening agent and lemon flavor as a flavoring agent. The prepared granules were evaluated for flow properties and compressed tablets for hardness, friability, content uniformity, weight variation, DT and in-vitro drug release. Instrumental analysis like FTIR, DSC and XRD was also performed. The flow properties of the granules of batch F6 were found to be excellent based on the results obtained. The weight variation and content uniformity of the tablets was found to be excellent F6 due to the excellent flow properties of the granules. All of the tablets in the study disintegrated between 22 (F6) to 135 seconds (F1), meeting the official requirement (3 minute) for dispersible tablets. The optimized batch showed complete drug release within 10 minutes time period. The FTIR and DSC study found no incompatibility between the drug excipients. The MOX in the final formulation was present in crystalline form, as shown by XRD. The dispersible MOX tablets could be a better option for treating pediatric TB.